Static analysis of functionally graded plate using non-linear classical plate theory with Von-Karman strains - Singh, S.J.; Harsha, S.P. (Zielona Góra: Uniwersytet Zielonogórski)
The present study is based on the nonlinear bending analysis of an FGM plate with Von-Karman strain based on the non-linear classical plate theory (NLCPT) with in-plane displacement and moderate rotation. Non-linear bending analysis based on stresses and transverse deflections is then carried out for the plate for the complex solution obtained using an analytical method viz. Navier`s method.
Keywords: functionally graded materials (FGM) plate; Von-Karman strain; nonlinear classical plate theory (NLCPT); Navier`s method